Evaluation of agricultural products e-commerce logistics service capabilities in Heilongjiang Province based on entropy weight TOPSIS method. - Wei Chen; Huan Chen; Jianhui Yin; Weinan Sun (PLoS ONE)
This study aims to evaluate the current status and relative advantages of the logistics service capabilities of agricultural products e-commerce in Heilongjiang Province, identify its development shortcomings and propose optimization paths. In the context of the rapid development of agricultural products e-commerce, logistics service capabilities have become a key factor affecting regional agricultural competitiveness and e-commerce efficiency. However, current related studies mostly focus on the macro level and lack a systematic evaluation of regional and long-term dynamics. To fill this research gap, this paper constructs a logistics service capability evaluation index system covering four dimensions: logistics foundation, operational efficiency, service quality and information level, which is refined into 12 third-level indicators. Using the entropy weight-TOPSIS method, this paper conducts longitudinal trend analysis and horizontal regional comparison based on the time series data of Heilongjiang Province from 2013 to 2022 and the cross-sectional data of 31 provinces and cities across the country in 2022. The study found that the logistics service capabilities of agricultural products e-commerce in Heilongjiang Province have shown a steady upward trend, especially in regional linkage and cold chain system construction. However, compared with developed regions in the country, there are still obvious gaps in infrastructure, digital management and terminal distribution efficiency. The main constraints include insufficient cold chain coverage, unreasonable layout of urban and rural logistics networks, and low technical integration. The findings of this study reveal the key bottlenecks in improving regional e-commerce logistics service capabilities, and put forward policy recommendations for strengthening the cold chain logistics system, optimizing urban and rural logistics layout, and promoting digital transformation. The study not only provides a theoretical basis and practical guide for improving the efficiency of agricultural product e-commerce logistics in Heilongjiang Province, but also provides experience for other major agricultural production areas to explore high-quality development paths, which has important practical significance and policy value.